Pediatric adrenal incidentaloma as a rare and difficult to diagnose finding - review - Pałac, Dominika; Ostrowska, Magdalena; Grześk-Kaczyńska, Magdalena; Kaczyński, Szymon (Journal of Education, Health and Sport, 2022)
Adrenal incidentaloma (AI) is an asymptomatic mass localized in the adrenal gland, usually detected during diagnostic imaging performed due to other health issues than the suspected adrenal disease. It occurs in 2% of adults and 0,2% of children. Pediatric AI may cause many difficulties in the diagnostic processes. Neuroblastoma is one of the most common malignant tumors in children. Usually, it is localized in the medulla of the adrenal gland. Many patients do not have any symptoms, but some may present with fever, weariness, weight loss, pain, enlarging mass, etc. The majority of cases are high- risk and the survival rate is less than 50%. The diagnostic protocol consists of laboratory tests and radiological imagining. Treatment depends on the risk group that the patient is assigned to. Pheochromocytoma is a rare catecholamine-secreting tumor in children originating in the adrenal medulla. Most pediatric patients present with sustained hypertension. 60% of pheochromocytoma cases are sporadic. The surgical removal of the tumor through adrenalectomy is a standard procedure. To the group of pediatric adrenocortical tumors (ACT), benign adrenocortical adenoma (ACA) and malignant adrenocortical carcinoma (ACC) are included. ACA is found in only 20% of cases of ACT. Most of the patients present with signs of virilization, Cushing Syndrome, or both. The 5-years survival rate of ACC in the pediatric population is 46-55%. An adrenal incidentaloma is an unpredictable and possibly dangerous disorder in the pediatric population. Due to the rarity of the finding and their variety, there is not much data and clear recommendations about AI management. Doctors need to know about the prevalence of different types of adrenal tumors in the pediatric population based on age.